“That’s How You Know He’s Your Love”: The Male Singing Voice and Disney’s (Re)interpretation of the Male Romantic Lead (Sound Stage Screen, 2023)
While romantic love is a central topic in most Disney films, love duets sung by the featured couple are relatively rare and solo songs sung by the male protagonist even rarer. The combination of masculinity and the musical expression of romantic feelings seems thus to pose a challenge. In order to understand the complexity of romantic masculinity in Disney movies it makes sense to consider an aspect that has so far been left unconsidered: the male singing voice. This article conducts a comparative analysis of the love duets “A Whole New World” from Aladdin (1992) and “I See the Light” from Tangled (2010), as well as the solo love songs “Lost in the Woods” from Frozen II (2019) and “Heaven’s Light” from The Hunchback of Notre Dame (1996). It focuses on three central questions: (1) whether various models of romantic masculinity are mirrored in specific stylistic musical or vocal devices; (2) how these connections relate to the longstanding tradition of voice categories (Stimmfach) in opera; and (3) in which ways the music and especially the singing comment on or even contradict the portrayed masculinity. By discussing the male lead as a musical character, the article offers a new perspective on Disney’s (re)interpretation of romantic masculinity.
Keywords: Masculinity; singing voice; Stimmfach; Disney; Gender